(3bWH GdSQhQ aj ChUGa GdNehQs - (3CHhESMGb EHQGgje Hf GdbGSe, GdeYQha HGdQbjb GdfOje, Ch GHf GdQbjb GdbjQhGfj,J (B425 (3g` s
(3ChdgG (B:s
(3bGd GdYJGHj(B: (3HYK Edqj WGgQ Hf GdMSjf aj jhe OLf aONdJ Ydjg, hHjf jOjg NGOe jSbjg, s
(3BNQgG (B:s
(3hoJQjg GdZnqj oQTOkG hJQjg GdoQTO ZnqjG Je GdLRA GdKGfj ef cJGH bWH GdSQhQ aj ChUGa GdNehQ s
(3ChdgG Jedc eDQN SfI (B859(3g`s
(3HgG VHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B57 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B67s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B128 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1351s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs